Test the Effectiveness of Eco-Enzyme Bioremediation as a Reducing Agent for Natural Stone Waste on Rice Plant Productivity and Water Quality in Dukupuntang District - Eviyati, Raden; Amini, Zakiyah; Wahana, Siti (Jurnal Agrosci, 2023)
Water is a natural resource that is needed for all living things. Likewise with the river used for irrigation of agricultural land. The Cigayem River is located in Dukupuntang District, Cirebon Regency. Above the river there are many natural stone cottage industries. The processing of natural stone into decorative stone requires a lot of water for its processing, so that a lot of river water in this area is polluted from this home industry activity. The waste is in the form of powder cut from natural stone with water which is directly channeled into irrigation canals without being processed first. The effect is siltation of irrigation canals and decreased water quality. This decrease in water quality has an impact on rice productivity in heavily affected areas. Pollution that occurs in irrigation canals in the study area can be identified by physical changes such as color and other impacts such as decreased productivity of rice yields in the study area since the establishment of the natural stone industry. The decline in rice productivity will threaten the sustainability of rice farming in central areas. Wastewater treatment technology has been developed a lot, but not all home industries can carry out waste treatment at a high cost. Eco enzyme can be a solution to waste pollution that pollutes rivers at a relatively low cost, easy to obtain and sustainable because all materials do not contain harmful chemicals and residues.